Penerapan model pembelajaran react (relating, experiencing, applying, cooperating, transfering) untuk meningkatkan keterampilan menulis teks nonfiksi peserta didik kelas V C sekolah dasar - Salsabila As-Shofa Un-Nisa; Hartono Hartono; Karsono Karsono (Universitas Sebelas Maret, 2020)
The purpose of this research is to improve nonfiction text writing skills at V C students of Djama’atul Ichwan Elementary School by REACT learning model. This research uses Classroom Action Research (CAR) method. The research was conducted in three cycles. Each cycle consists of one meeting. There are four stages that are passed in each cycle. The stages are a) planning, b) implementation of actions, c) observation, and d) reflection. The subject of this research was a teacher and 22 students of class V C. Data in this reseacrh were collected through interview, tests, observations, and documentations. The data then tested foe validity by data triangulation and techniques triangulation. Miles & Huberman interactive analysis is used as a data analysis technique in this research. The minimum completeness criteria for Indonesian subjects was 75. The results showed classical completeness in the first cycle was 52,38%, increased again to 80,95% in the second cycle, and in the third cycle the clasical completeness was 86,36%. Based on the results obtained, it can be seen that the application of the REACT learning model can improve the nonfiction text writing skills of elementary school students in Surakarta in the 2019/2020 school year.